Sistem Informasi Geografis Pemetaan Wisata di Kabupaten Solok - Ratino, Abel; ., Sularno; Sahrun, Nori (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
This research focuses on the design and implementation of a Geographic Information System (GIS) for tourism mapping in Solok Regency. Involving user needs analysis, spatial data collection, and the development of a web-based GIS application, the research aims to enhance tourism information management. The system provides a clear visualization of tourist attractions and supporting facilities, with the goal of enriching the tourist experience and supporting tourism management decisions. The advantages of this GIS include easy navigation and the ability to present comprehensive tourism information, expected to strengthen the tourism infrastructure of Solok Regency and support sustainable promotion and management of tourism resources.